2004
DOI: 10.1002/art.20380
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of mutant tumor necrosis factor receptor superfamily 1A associated with tumor necrosis factor receptor–associated periodic syndrome: Differences between cell types

Abstract: Objective. To investigate the effect of mutations in tumor necrosis factor receptor superfamily 1A (TNFRSF1A) on the ability of the receptors to be cleaved from the cell surface upon stimulation. The mutations we studied are associated with clinically distinct forms of TNF receptor-associated periodic syndrome (TRAPS). We also investigated different cell types within the same form of TRAPS.Methods. The shedding of TNFRSF1A in response to stimulation with phorbol myristate acetate was assessed in leukocytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 25 publications
7
64
0
3
Order By: Relevance
“…Peripheral blood leukocytes from TRAPS patients with T50M and T50K variants showed defective TNFRI shedding (3,17). However, it has recently been reported that variations in TNFRI shedding are not only related to the structural mutations in TNFRI, but may also depend on other cellular factors (16).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Peripheral blood leukocytes from TRAPS patients with T50M and T50K variants showed defective TNFRI shedding (3,17). However, it has recently been reported that variations in TNFRI shedding are not only related to the structural mutations in TNFRI, but may also depend on other cellular factors (16).…”
Section: Discussionmentioning
confidence: 96%
“…In recent studies, Huggins et al (16) and Todd et al (15) analyzed HEK 293 cells stably transfected with truncated WT TNFRI and TRAPS-associated TNFRI variants lacking the cytoplasmic regions and showed that the surface expression of the T50M variant was similar to that observed for the WT receptor. Moreover, the full-length T50M variant was also expressed on the cell surface, although at a lower level than that of the WT TNFRI.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The TNFR1 is present physiologically in both the soluble (sTNFR1) and membrane (mTNFR1) bound form, both of which are decreased in TRAPS patients [15][16][17][18][19][20]. These observations suggest either defective receptor shedding or defective trafficking of mutant receptors to the cell surface.…”
Section: Autoinflamamatory Diseases Linked To Disorders In Protein MImentioning
confidence: 99%